PENGELOLAAN SISTEM INFORMASI MANAJEMEN PERPUSTAKAAN BERBASIS E-LIBRARY PADA DINAS PERPUSTAKAAN DAN ARSIP KOTA BALIKPAPAN - Gea Cita Meiratri; Bambang Irawan; Muhammad Zaini (Journal of Policy & Bureaucracy Management, 2020)
The existence of the e-library-based library is expected to be able to answer information needs and provide activities and reading materials that are interesting for the public. The purpose of this research is to find out and describe the management information system of e-library-based library in the Balikpapan City Library and Archieves Service (Dinas Perpustakaan dan Arsip Kota Balikpapan – in Indonesian), namely in planning, organizing, application (input, process and output_ and evaluation in accordance with applicable rules and procedures. By using a qualitative descriptive method, the result of the research show that the Balikpapan City Library and Archieves Service has implemented management information system, although have not been maximally managed. The management of management information system still hampered by a lack of public understanding of the internet and cannot use electronic goods. Therefore, researchers provide a solution to increase the number of e-books in the application and improve closer and routine socialization to the public regarding the use of the iBalikpapan application.